Economic Sociology : A Systematic Inquiry - Portes, Alejandro, 1944- (Book collections on Project MUSE., 2010)
The sociological study of economic activity has witnessed a significant resurgence. Recent texts have chronicled economic sociology's nineteenth-century origins while pointing to the importance of context and power in economic life, yet the field lacks a clear understanding of the role that concepts at different levels of abstraction play in its organization. Economic Sociology fills this critical gap by surveying the current state of the field while advancing a framework for further theoretical development. Alejandro Portes examines economic sociology's principal assumptions, key explanatory concepts, and selected research sites. He argues that economic activity is embedded in social and cultural relations, but also that power and the unintended consequences of rational purposive action must be factored in when seeking to explain or predict economic behavior.